1994
DOI: 10.1002/eji.1830240629
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 prevents experimental allergic encephalomyelitis in rats

Abstract: Experimental allergic encephalomyelitis (EAE) is an autoimmune disease mediated by myelin protein-specific CD4+ T lymphocytes of the T(h)1-like phenotype. In rats, the disease is characterized by a monophasic clinical manifestation, followed by a subsequent spontaneous remission and the establishment of life-long resistance to reinduction of disease. Recent data indicate that intracerebral cytokine production, in particular synthesis of interleukin(IL)-10, is selectively up-regulated during the recovery phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(150 citation statements)
references
References 37 publications
6
143
0
1
Order By: Relevance
“…Previous studies are unclear about the role of IL-10 in recovery from EAE. One study in the rat (Rott et al, 1994) found that exogenous IL-10 reduced the severity of EAE, whereas another study, in mice, found the opposite (Cannella et al, 1996). Thus, we found increased expression of all cytokines, relative to the expression of -actin, during late clinical recovery, near the time that spontaneous relapses of EAE can occur.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies are unclear about the role of IL-10 in recovery from EAE. One study in the rat (Rott et al, 1994) found that exogenous IL-10 reduced the severity of EAE, whereas another study, in mice, found the opposite (Cannella et al, 1996). Thus, we found increased expression of all cytokines, relative to the expression of -actin, during late clinical recovery, near the time that spontaneous relapses of EAE can occur.…”
Section: Discussionsupporting
confidence: 43%
“…IL-10 has been shown to have a half-life of around 2 h in vivo (21) and a previous study administering large quantities of IL-10 frequently, showed that EAE could be prevented when administered systemically during the priming phase of EAE (6). However, should IL-10 be of therapeutic benefit, then it should be administered once the autoaggressive response has already been generated.…”
Section: Discussionmentioning
confidence: 99%
“…I nterleukin-10 is an immunoregulatory cytokine that has been shown to possess potential therapeutic value for organ-specific autoimmune diseases, as it reduces symptoms of experimental diabetes (1,2), autoimmune encephalomyelitis (3,4), inflammatory bowel disease (5), and autoimmune arthritis (6 -9).…”
mentioning
confidence: 99%